PEMBERIAN LAYANAN KONSELING KELOMPOK UNTUK MENGATASI PERILAKU CYBERBULLYING DI SMP NEGERI 6 BINJAI - Siti Rianti Rizki Utami (Al-Mursyid : Jurnal Ikatan Alumni Bimbingan dan Konseling Islam (IKABKI), 2020)
This study aims to determine the provision of group counseseling services to overcome cyberbullying behavior in SMP Negeri 6 Binjai. In the research the data collection method used was a questionnaire and the subjects of this study were 16 students at SMP Negeri 6 Binjai who were perpetrators of cyberbullying. Ftom the results of the t test statistical analysis it is known that there is a significant difference in cyberbullying between the pre-test and post-test conditions as shown by the magnitude of the coefficient t = 6.318 with p < 0.05. This means that group counseling has a significant effect on decreasing cyberbullying behavior in students.Keyword: Cyberbullying, Group Counseling